Classical Trajectory Calculations of Infrared Multiphoton Absorption and Dissociation. Issue 4 (1985) - Gray, S. K.; Stine, J. R.; Noid, D. W.
Abstract : A review of classical trajectory calculations of infrared multiphoton absorption and dissociation is presented. These calculations have demonstrated that the classical method can be useful for interpreting experimental results and for understanding the fundamental processes by which molecules absorb photons from the laser.